Productive Program of The Enterprise: Content, Influence Factors and Formation Procedure - NOVICHENKO, L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The strategic plan for the development of the enterprise and the implementation of operational objectives of the entity directly depend on the formation of the optimal production program of the enterprise. The flexibility and ability of the enterprise to quickly adapt to changes in the market environment, ensuring compliance with production indicators and product sales plan are based on factors that positively and negatively affect the implementation of the production program. The production program of the enterprise is one of the key elements of ensuring the rhythm of production and reducing the lost capacity of the business entity, adapting to changes in market conditions with the least losses. The main purpose of writing the article is to substantiate the theoretical provisions for determining the content of the production program of the enterprise, systematization of factors and development of practical recommendations for improving the formation of indicators of the production program taking into account the profile of the business entity. The article presents the theoretical justification and definition of the economic content of the “production program”. The factors influencing the formation of indicators of the production program of the enterprise are considered, their systematization is offered. The approaches of scientists to the selected stages and the algorithm for forming the optimal production program of the enterprise in a market environment are studied. It is established that the market analysis and factor analysis of the production program is the basis for ensuring its optimal structure in terms of resource conservation and existing market constraints. The list of stages of the order of development of the production program on the basis of application of the system approach and the account of criteria of optimality that promotes rational performance of indicators of the sales plan with the least expenses of resources is offered.